Assess of Quality of Blood Culture Testing - A Survey in Intensive Care Units and Microbiological Laboratories - Abdulaziz Eid Alharbi,; Hashim Marshud Alsaedi,; Amlak Aziz Almutairi,; Talal Mohammad Albdoor, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Blood culture (BC) testing before starting antimicrobial therapy is an internationally recommended practice for sepsis management, essential for reducing ICU stays and a core component of antibiotic stewardship programs. However, BC testing faces limitations, including low pathogen detection rates and challenges in standardizing preanalytic procedures, which impact diagnostic accuracy and vary across healthcare systems. Methods: This study conducted a qualitative survey across 138 interviews with ICU and microbiological laboratory (LAB) staff . The survey assessed current BC testing practices, including sepsis awareness, preanalytic procedures, sampling techniques, and result communication. Interviews were conducted via telephone by an independent agency, with data collected from ICU and LAB directors, residents, nurses, and managersthorough four hospital. Results: Sepsis awareness was consistently high across countries, but BC testing practices varied significantly. In first hospital BC collection and transport were more streamlined, with LABs frequently open on weekends and ICU physicians responsible for sampling and antibiotic decisions. In contrast, another hospital reported notable preanalytic deficiencies, including delayed BC transport, insufficient blood volumes, and limited clinician responsiveness. The other two hospitals showed distinct procedural differences, with issues such as financial constraints impacting BC quality . Variability in blood volumes, transport times, and sample handling affected BC positivity rates and pathogen detection across the four countries. Conclusion: This study reveals significant disparities in BC testing practices across different hospitals ICUs and microbiological laboratories. Improving BC test accuracy will require addressing preanalytic limitations through standardized protocols, optimized sampling procedures, and better communication between ICU and LAB staff. Enhanced awareness and training on preanalytic protocols may improve diagnostic yield and support more effective sepsis management.